Effectiveness of Teacher Professional Education Program (PPG) of UIN Datokarama Palu from Students' Perspective (A Mixed Method Approach) - Erniati, Erniati; Nadirah, Sitti; Nurdin, Nurdin; Ubadah, Ubadah; Anirah, Andi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to investigate PPG students' perceptions regarding the program's effective implementation at UIN Datokarama Palu and identify factors that affect the program's effectiveness. The research method used is a mixed method in which we simultaneously employed quantitative and qualitative methods. We surveyed the distribution of questionnaires using Google Forms and conducted in-depth interviews with several PPG students. The results indicate that most students consider the PPG relevant to improving teachers’ competencies and skills. The competencies include selecting, planning, developing, using, and actualizing various classroom teaching materials. Meanwhile, the skills include practicing digital learning and choosing and using relevant teaching material in digital format. However, various obstacles still exist, such as the lack of active interaction in learning, internet connection issues, and the mismatch between task load and available time. Based on the findings, this study recommends improving technological infrastructure, strengthening mentoring, and re-evaluating the curriculum and program management to enhance the Effectiveness of PPG in the future. Future studies should focus on increasing PPG students’ engagement experience during the online PPG program delivery.